2022
DOI: 10.1186/s41687-022-00512-4
|View full text |Cite
|
Sign up to set email alerts
|

Development of the multidimensional health perceptions questionnaire in English and Spanish

Abstract: Purpose To develop the novel multidimensional health perceptions questionnaire (MHPQ), a self-reported assessment of health perceptions inclusive of (1) individuals beliefs about the causes and consequences of health conditions, benefits and barriers to maintaining and improving health, ability to accomplish health-related goals and control health circumstances, and the role of God and/or spirituality in health and healthcare, (2) anticipated discrimination in the healthcare systems, and (3) tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…22 Cognitive interviews are commonly used and play an important role in evaluating survey instruments, particularly when translation is involved. [22][23][24][25] When cross-cultural equivalency is ignored, a serious threat to the comparability of survey results between different language speakers can occur, which limits the usability of the data. 21 Furthermore, it is especially important to assess the reliability of transcreated measures for understandability and cultural sensitivity before use in larger studies.…”
Section: Background and Significancementioning
confidence: 99%
See 1 more Smart Citation
“…22 Cognitive interviews are commonly used and play an important role in evaluating survey instruments, particularly when translation is involved. [22][23][24][25] When cross-cultural equivalency is ignored, a serious threat to the comparability of survey results between different language speakers can occur, which limits the usability of the data. 21 Furthermore, it is especially important to assess the reliability of transcreated measures for understandability and cultural sensitivity before use in larger studies.…”
Section: Background and Significancementioning
confidence: 99%
“…Pilot testing in the target population is a crucial step to ensure that the transcreated items are equivalent to the source items,21 identify any problems that respondents have in understanding or responding to questions, and revise to improve participant understanding and ability to respond to survey items 22. Cognitive interviews are commonly used and play an important role in evaluating survey instruments, particularly when translation is involved 22-25. When cross-cultural equivalency is ignored, a serious threat to the comparability of survey results between different language speakers can occur, which limits the usability of the data 21.…”
Section: Background and Significancementioning
confidence: 99%
“…There are documented examples of ways in which the US healthcare system can impact individuals’ healthcare utilization, including vaccination intentions. Previous studies found that individuals’ perceptions of the healthcare system were important drivers of intentions to use healthcare services 11 (e.g., when individuals perceived barriers to their healthcare and/or concerns over receiving equal treatment, they were less likely to engage with the healthcare system 12–14 ). In many cases, negative perceptions of the healthcare system decreased intentions to vaccinate.…”
mentioning
confidence: 99%